2012
DOI: 10.1089/scd.2010.0539
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb Group Protein Bmi1 Promotes Hematopoietic Cell Development from Embryonic Stem Cells

Abstract: Bmi1 is a component of the Polycomb repressive complexes and essential for maintaining the pool of adult stem cells. Polycomb repressive complexes are key regulators for embryonic development by modifying chromatin architecture and maintaining gene repression. To assess the role of Bmi1 in pluripotent stem cells and on exit from pluripotency during differentiation, we studied forced Bmi1 expression in mouse embryonic stem cells (ESC). We found that ESC do not express detectable levels of Bmi1 RNA and protein a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…The Pcgf component of these PRC1 subtypes is of special interest as they define specific PRC1 functions indicated by genome‐wide chromatin binding . The expression of PRC1 complex components changes during ESC differentiation and consequently different PRC1 complexes with different subunit compositions assemble . In agreement we observed that upon ESC differentiation Pcgf6 expression ceased and alternative Pcgf paralogs become expressed.…”
Section: Discussionsupporting
confidence: 82%
“…The Pcgf component of these PRC1 subtypes is of special interest as they define specific PRC1 functions indicated by genome‐wide chromatin binding . The expression of PRC1 complex components changes during ESC differentiation and consequently different PRC1 complexes with different subunit compositions assemble . In agreement we observed that upon ESC differentiation Pcgf6 expression ceased and alternative Pcgf paralogs become expressed.…”
Section: Discussionsupporting
confidence: 82%
“…In our previous work, we showed that forced Bmi1 expression promotes hematopoietic cell development from ES cells [26]. We also found that Bmi1 can efficiently substitute for c-Myc in iPS cell generation (unpublished data).…”
Section: Discussionmentioning
confidence: 77%
“…ES cells (HM1) and iPS cells were cultured, as described previously [26,27]. Briefly, cells were maintained on inactivated MEF feeder layer from C57BL/6 mice with ES cell medium.…”
Section: Cells and Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Other groups reported efficient generation of cells that mostly produce the myeloid lineage following long term engraftment or produce CD34+ hematopoietic precursors that have phenotype similar to adult HSC but might best correspond to the embryonic stage of yolk-sac, aortogonadalmesonephros (AGM), and/or fetal liver stage of hematopoiesis (Melichar et al, 2011;Narayan et al, 2006 andfor review : Tian andKaufman, 2008). More recently, the polycomb group protein Bmi1 was shown to promote more than 100-fold increase of hematopoietic cell development from ESC (Ding et al, 2011).…”
Section: Obtaining Hsc From Escmentioning
confidence: 99%